Excessive daytime sleepiness in patients with depressive disorder - Chellappa,Sarah Laxhmi (2006)
OBJECTIVE: To evaluate excessive daytime sleepiness in patients with depressive disorder and to examine its association with the severity of depression and suicidal ideation. METHOD: Seventy patients were interviewed and assessed by the Epworth Sleepiness Scale (ESS), the Beck Depression Inventory (BDI) and the Beck Scale for Suicidal Ideation (SSI). Descriptive analysis, Pearson correlations and Student's t-test were used for data analyses. RESULTS: Most of the patients (57.1%) obtained high scores on the ESS. Correlation was positive and strongly significant between ESS scores and BDI scores, as well as between ESS scores and SSI scores. Patients with high ESS scores obtained higher mean BDI and SSI scores in comparison to patients with lower ESS scores. Significant differences (p < 0.05) were encountered when the patients with higher (>10) and lower (< 10) ESS scores were compared in terms of total ESS, BDI and SSI scores. CONCLUSIONS: Excessive daytime sleepiness was frequent among patients and significantly associated with higher levels of depression and particularly with suicidal ideation. Thus, a careful investigation of daytime sleepiness in depressed patients is required during clinical evaluation.